Recurrent rhino-ocular-cerebral mucormycosis in a leukemic child: a case report and review of pediatric literature - Francesco De Leonardis; Teresa Perillo; Giuseppe Giudice; Gianfranco Favia; Nicola Santoro (MDPI AG, 2015)
Mucormycosis is an uncommon but severe fungal infection, typically observed in immunocompromized patients. We report a case of acute lymphoblastic leukemia complicated by rhino-oculo-cerebral mucormycosis in a pediatric patient. Combination lipid polyeneechinocandin therapy, along with surgical debridement appeared to be effective. Nevertheless, a severe relapse occurred during posaconazole prophylaxis; antifungal therapy, hemimaxillectomy and suspension of chemotherapy were performed. Although mucormycosis is a frequently lethal infection, prompt diagnosis and aggressive treatment can be successful even in cases of relapse.